VCII-Based Transimpedance-Mode All Pass Filter using Single Grounded Capacitor - Burin Theppota; Winai Jaikla; Wiset Saksiri; Montree Siripruchyanun (My University, 2024)
This paper describes a first-order transimpedance-mode all-pass filter (APF) based on single grounded capacitor and second-generation voltage conveyors (VCIIs). The proposed APF comprises 3 VCIIs cooperating with 5 resistors and 1 grounded capacitor, it is consequently suitable to integrated circuit implementation. The phase angle of the output relative to input signals can be tuned by the external resistors. In addition, the amplitude of output voltage can be linearly controllable by a resistor. The output current can also be achieved to offer current-mode APF without changing circuit topology. The proposed APF offers a phase shifting function over a wide range of operating frequency. Its output also provides an accurate sinusoidal signal. The testing results obtained from PSpice simulation are disclosed to investigate different behaviors of the proposed APF. From the results, it is found that they are agreed well with the mentioned anticipations, where its total power consumption is about 1.02mW at ±1.2V supply voltages.
Keywords: Analog and Mixed-Signal Circuit Design; Neural Networks and Applications; Advanced Adaptive Filtering Techniques